MAHKOTA SEJARAH: JEJAK PENDIDIKAN ISLAM DI SULAWESI PADA MASA AWAL - Mukjizah Mukjizah; Bahaking Rama; Asgar Marzuki (CV. ADIBA AISHA AMIRA, 2025)
This study aims to explore and clarify studies related to the development of early Islam in Sulawesi, the role of educational institutions and figures in the development of Islamic education in Sulawesi. The method used is to use literature study. The results of the study show that the history of Islamic education begins at the same time as the development of Islamic history. In the long course of Islamic history, Islamic education has also experienced various fluctuating dynamics along with fluctuations in Islamic history itself. Almost all Islamic educational institutions in Indonesia prohibit peace and goodness. In each phase, Islamic education develops with diflerent characteristics. There are two figures who provide renewal of Islamic education in Sulawesi, namely AGH. Abdullah Dahlan bin Abdurrahman and AGH. Muhammad As'ad. In addition, there is informal education in Sulawesi, namely by strengthening the integration of Islamic law (sara') in the panngaderreng system and (2) organizing Islamic education in mosques and formal education with education in Islamic boarding schools and madrasas.